2014
DOI: 10.1111/ecge.12079
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Competition and Interdependence in Strategic Decisions: Empirical Evidence from Franchising

Abstract: This paper investigates spatial competition and spatial interdependence in two key strategic variables in franchising: the proportion of franchised outlets (franchise proportion) and the royalty rate. Employing a simultaneous equations model and data from 353 U.S.franchise chains in 43 sectors in 2005, we find robust evidence for significant spatial competition and stable interdependence in these two strategic variables. Specifically, we find spatial competition in each strategic variable, and spatial interdep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 46 publications
0
2
0
1
Order By: Relevance
“…A study by Yawson et al for the UK found that while spring barley production would benefit under climate change, the total land area allocated to barley production would determine whether it can be self-sufficiency, and the UK could face a large deficit in domestic feed barley production if the area is not expanded [21]. At the same time, most studies point out that arable land resources per capita and technological progress are important factors influencing changes in GP [22][23][24]. In addition, factors such as climate change [25], labor force changes [26], fertilizer application [27], economic and social environment [28] and urbanization [29] also affect GP to varying degrees.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Yawson et al for the UK found that while spring barley production would benefit under climate change, the total land area allocated to barley production would determine whether it can be self-sufficiency, and the UK could face a large deficit in domestic feed barley production if the area is not expanded [21]. At the same time, most studies point out that arable land resources per capita and technological progress are important factors influencing changes in GP [22][23][24]. In addition, factors such as climate change [25], labor force changes [26], fertilizer application [27], economic and social environment [28] and urbanization [29] also affect GP to varying degrees.…”
Section: Introductionmentioning
confidence: 99%
“…In the process of constructing the conflict measurement model of PLES in Wuhan, we refer to existing studies to construct the spatial conflict model from the perspective of spatial complexity, vulnerability, and stability based on landscape ecological theory (Liao et al, 2017;. In addition, some scholars have built a spatial conflict measurement model from the perspectives of spatial types, spatial patterns, and spatial processes based on geographical theory (Chen et al, 2014;He et al, 2014). Through the comparison of the two points of view, the conflict index is constructed based on landscape ecology theory to better reflect the changes in the landscape environment caused by spatial conflict.…”
Section: Construction Of the Spatial Conflict Modelmentioning
confidence: 99%
“…Estudos recentes têm proposto que a decisão quanto ao mix contratual e royalties são decisões conjuntamente estabelecidas (CHEN et al, 2015). Menores taxas de royalties estão associadas a uma maior proporção de lojas franqueadas, relação essa prevista como estável na medida em que as redes amadurecem.…”
Section: Resultsunclassified